Social Networks and Surveillance for Society - Özyer, Tansel; Bakshi, Sambit; Alhajj, Reda.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on recent technical advancements and state-of-the art technologies for analyzing characteristic features and probabilistic modelling of complex social networks and decentralized online network architectures. Such research results in applications related to surveillance and privacy, fraud analysis, cyber forensics, propaganda campaigns, as well as for online social networks such as Facebook. The text illustrates the benefits of using advanced social network analysis methods through application case studies based on practical test results from synthetic and real-world data. This book will appeal to researchers and students working in these areas. .
Chapter1. Frauds in Online Social Networks: A Review -- Chapter2. Leveraging Social Network Analysis and Cyber Forensics Approaches to Study Cyber Propaganda Campaigns -- Chapter3. Hiding Self on Facebook Sidebar Ticker, Surveillance and Privacy -- Chapter4. Identifying In uential Spreaders in Complex Networks with Probabilistic Links -- Chapter5. Decentralized Online Social Networks Architectures -- Chapter6. We Shall Not Only Survive To The Future of Social Networks -- Chapter7. A Centrality Measure for Directed Networks: m - Ranking Method -- Chapter8. Searching on Facebook Through the Lens of the Concept of Privacy -- Chapter9. Emergency Detection and Evacuation Planning Using Social Media -- Chapter10. Social Network Analysis to Combat Terrorism: 2015 Paris Attacks.
Keywords: Sociology -- Methodology; Data mining; Social media; Social sciences -- Data processing; Sociological Methods; Data Mining and Knowledge Discovery; Social Media; Computer Application in Social and Behavioral Sciences